The Use of Distance Technologies in Teaching Children with Autism Spectrum Disorders - N.Y. Guseva; O.S. Piskareva (Moscow State University of Psychology and Education, 2020)
The article describes some aspects of the organization and application of distance learning for children with autism spectrum disorder (ASD) in a Regional Resource Center for Supporting Children with ASD in Nizhny Novgorod Region (RRC). Due to the temporary need for a complete transition to distance learning, a series of classes developed using computer technology. Aspects of the organization and application of distance learning in the Regional Resource Center for Supporting Children with ASD (RRC) of Nizhny Novgorod are described: the inclusion of parents in the training, the implementation of a differentiated approach to learning, the possibility of forming various skills in children with ASD in an interactive mode. Currently, the use of computer technology in the education of children with ASD is not sufficiently developed to be able to use the finished product. The RRC has developed a set of classes using computer technologies, aimed at the general development of cognitive functions and specific educational skills of this category of children. 30 families with children with ASD aged from 5 to 10 years participated in the use of the proposed technologies. Implementation experience has shown that computer technology allows children with ASD to quickly and efficiently master and consolidate material in an educational-game form. The developed materials will be able to increase the productivity of full-time classes, supplementing them with the possibility of consolidating the acquired knowledge and skills at home.